Casing and liners for drilling and completion - Byrom, Ted G. (Gulf drilling series., 2007)
The Gulf Drilling Series is a joint project between Gulf Publishing Company and the International Association of Drilling Contractors. The first text in this Series presents casing design and mechanics in a concise, two-part format. The first part focuses on basic casing design and instructs engineers and engineering students how to design a safe casing string. The second part covers more advanced material and special problems in casing design in a user-friendly format. Learn how to select sizes and setting depths to achieve well objectives, determine casing loads for design purposes, design casing properties to meet burst, collapse and tensile strength requirements and conduct casing running operations safely and successfully.